Non-targeted metabolomic reveals the effect of salt stress on global metabolite of halotolerant yeast Candida versatilis and principal component analysis. (1st October 2014) - Qi, Wei; Fan, Zhen-Chuan; Wang, Chun-Ling; Hou, Li-Hua; Liu, Jin-Fu; Cao, Xiao-Hong
Abstract: As one of the major microbes in the soy sauce fermentation, Candida versatilis enriches the flavor and improves the quality of soy sauce. In this study, a combination of five different GC-MS and LC-MS-based metabolome analytical approaches was used to analyze the intracellular, extracellular and whole metabolites of C. versatilis . Our results found out that a total of 132, 244 and 267 different metabolites were detectable from the intracellular, extracellular and whole part, respectively. When exposed to 0. 9 and 18 % salt, respectively, 114, 123 and 129 different intracellular metabolites, 184, 200 and 178 extracellular metabolites and 177, 188 and 186 whole metabolites were detected, respectively. Our data showed that salt enhances the metabolic capacity of C. versatilis, especially its amino acid and enhances the synthesis and secretion of some metabolites of C. versatilis, especially the aldehydes and phenols, such as vanillin, guaiacol and 5-hydroxymethylfurfural. Our data also showed that special attention has to be paid to the generation of biogenic amines when C. versatilis was treated with salt.